Estimation of the freezeout parameters using strange hadrons with changing multiplicity in pp collisions at 7 TeV - Ahmad, Hilal; Zhu, Hailong; Liu, Fu-Hu; Waqas, M.; Badshah, Murad; Ghodhbani, Refka (Frontiers in Physics, 2025)
We explore the spectra of transverse momenta of hadrons with strange quark content (KS0, ϕ, Λ+Λ̄, Ξ̄+Ξ̄+, and Ω−+Ω̄+) produced in proton–proton collisions at sNN = 7 TeV. We applied Tsallis statistics in a blast wave model (TBW) to the ALICE Collaboration’s experimental data and extracted the freezeout parameters (Tsallis temperature, transverse flow velocity, and the parameter q, which is the non-extensive parameter). The changing trend of these parameters is studied with changing multiplicity. The parameter q decreases while the parameter T and βT increases toward higher multiplicities. βT is noted to drop to zero in the system with the lowest multiplicities. In addition, the interrelationships between the parameters T with βT and T with q are presented where the former correlation is positive and the latter one is negative.